Anti-reflection and anti-reflection film on photovoltaic encapsulation glass surface and preparation method thereof

By using ALD technology to deposit ALD-TiO2/SiO2 composite layer on photovoltaic encapsulated glass materials, the problem of large light reflection loss is solved, and efficient photoelectric conversion and film stability and uniformity are achieved.

CN119330608BActive Publication Date: 2025-03-14EAST CHINA UNIV OF SCI & TECH +1

Patent Information

Application Number
CN202411886537.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-14
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The reflectivity of existing photovoltaic encapsulated glass materials is high, resulting in large light reflection loss, affecting photoelectric conversion efficiency, and it is difficult to achieve uniformity and conformity on complex-shaped substrates.

Method used

Atomic layer deposition technology (ALD technology) is used to deposit ALD-TiO2 seed layer and ALD-TiO2/SiO2 composite layer on the surface of the glass substrate. Through plasma activation and optimization of coating processes, a reduction and anti-reflection film with high uniformity and high adhesion is achieved.

Benefits of technology

It achieves an extremely high reduction and reverse-reflection effect, with a transmittance of 99.5%, and improves the durability and stability of the film, effectively reduces light loss, and improves the photoelectric conversion efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330608B_ABST
    Figure CN119330608B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of solar cell packaging, and specifically discloses an anti-reflection and anti-reflection film on the surface of photovoltaic packaging glass and a preparation method, comprising the following steps: S1, pre-cleaning of the surface of the glass substrate; S2, purging the surface of the glass substrate using a plasma generator; S3, depositing an ALD-TiO2 seed layer on the surface of the glass substrate using atomic layer deposition technology; S4, depositing an ALD-TiO2 / SiO2 composite layer on the upper surface of the ALD-TiO2 seed layer according to a certain thickness ratio. The present invention adopts the above-mentioned anti-reflection and anti-reflection film on the surface of photovoltaic packaging glass and a preparation method, the film has excellent anti-reflection and anti-reflection effect, and the film has high stability, uniformity and durability, effectively reduces light loss, and thus improves photoelectric conversion efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solar cell packaging, and in particular to an anti-reflection and anti-reflection film on the surface of photovoltaic packaging glass and a preparation method thereof. Background Art

[0002] The ordinary photovoltaic encapsulation glass of solar cells has a strong reflective effect on sunlight, which leads to a light reflection loss of nearly 10%, reduces the utilization of light energy, affects the power generation efficiency, and greatly reduces the photoelectric conversion efficiency of photovoltaic modules. In addition, the use of ordinary photovoltaic encapsulation glass affects the matching between its solar cells, which in turn affects the performance of the overall module. Therefore, in order to reduce light loss and improve photoelectric conversion efficiency, it is necessary to coat the surface of the encapsulation glass with an anti-reflection and anti-reflection film to improve performance.

[0003] In the prior art, photovoltaic encapsulation glass materials are coated with anti-reflection and anti-reflection films of materials such as silicon dioxide, titanium dioxide and aluminum oxide on their surfaces by sol-gel method, vacuum electron beam evaporation method and magnetron sputtering method to improve the photoelectric conversion efficiency. However, these methods are difficult to control the thickness and shape of the film very accurately, which leads to the production of too thick films. On the one hand, it will lead to reduced toughness of the film, poor adhesion, and easy defects such as cracks and peeling, causing film performance failure; on the other hand, it will also increase costs. In addition, these methods cannot achieve uniformity and conformality for photovoltaic encapsulation glass material substrates with complex shapes.

[0004] Therefore, the preparation of universal, high-performance anti-reflection and anti-reflection films is particularly critical to improving the photoelectric conversion efficiency of solar cells and optimizing component performance. Summary of the invention

[0005] The purpose of the present invention is to provide an anti-reflection and anti-reflection film on the surface of photovoltaic encapsulation glass and a preparation method thereof, wherein the film has excellent anti-reflection and anti-reflection effects, and the film has high stability, uniformity and durability, effectively reduces light loss, and thus improves photoelectric conversion efficiency.

[0006] To achieve the above object, the present invention provides a method for preparing an anti-reflection and anti-reflection film on the surface of photovoltaic encapsulation glass, comprising the following steps:

[0007] S1. Pre-cleaning of the glass substrate surface;

[0008] S2, using a plasma generating device to purge the surface of the glass substrate;

[0009] S3, depositing an ALD-TiO2 seed layer on the surface of the glass substrate using atomic layer deposition technology;

[0010] S4. Depositing an ALD-TiO2 / SiO2 composite layer on the upper surface of the ALD-TiO2 seed layer at a certain thickness ratio.

[0011] Preferably, S1 is specifically:

[0012] Deionized water is used to clean the surface of the glass substrate to remove impurities, and then the glass substrate is soaked and cleaned with an organic solvent, and then dried after cleaning.

[0013] Preferably, S2 is specifically:

[0014] The glass substrate was placed in the ALD chamber, and the plasma power of the plasma generator was set to 600 W. The surface of the glass substrate was purged with oxygen-argon mixed plasma for 10 min to 20 min.

[0015] Preferably, S3 is specifically:

[0016] In the ALD chamber, the temperature range is set to 90℃~120℃, the vacuum is 0Pa~20Pa, and argon is used as a carrier gas to alternately introduce a titanium precursor and an oxidant, and the ALD-TiO2 seed layer is obtained by multiple cycles of deposition.

[0017] Preferably, in S3, the set temperature is 100°C.

[0018] Preferably, in S3, the range of the multiple cycles of deposition is 100 to 1000 cycles.

[0019] Preferably, S4 is specifically:

[0020] S41, in the ALD chamber, using argon as a carrier, introducing a silicon precursor in the presence of plasma oxygen, and performing multiple cycles of deposition to obtain an ALD-SiO2 layer;

[0021] S42, using argon as a carrier gas, alternately introducing a titanium precursor and an oxidant, and performing multiple cycles of deposition to obtain an ALD-TiO2 layer;

[0022] S43, taking a layer of ALD-TiO2 deposited by multiple cycles and a layer of ALD-SiO2 deposited by multiple cycles as a whole, repeating several layers to obtain an ALD-TiO2 / SiO2 composite layer.

[0023] To achieve the above-mentioned purpose, the present invention also provides an anti-reflection and anti-reflection film on the surface of photovoltaic encapsulation glass.

[0024] Preferably, it includes a glass substrate and an ALD-TiO2 seed layer and an ALD-TiO2 / SiO2 composite layer sequentially arranged on the surface of the glass substrate, the ALD-TiO2 / SiO2 composite layer includes several ALD-SiO2 layers, and ALD-TiO2 layers are arranged between the ALD-SiO2 layers.

[0025] Preferably, the number of the ALD-SiO2 layers is three, and the thickness ratio of the ALD-TiO2 seed layer, ALD-SiO2 layer, ALD-TiO2 layer, ALD-SiO2 layer, ALD-TiO2 layer, and ALD-SiO2 layer is 5~16:30~40:45~54:15~17:35~44:95~103.

[0026] Therefore, the present invention adopts the above-mentioned anti-reflection and anti-reflection film on the surface of photovoltaic encapsulation glass and the preparation method, and the beneficial effects are as follows:

[0027] (1) The present invention adopts atomic layer deposition technology (ALD technology), which can achieve precise control at the atomic level, avoid the shortcomings of other processes, and form a highly uniform film layer on a substrate with a complex 3D surface. Therefore, it can prepare a highly uniform and dense TiO2 / SiO2 film on a glass substrate. This uniformity is crucial to achieving an ideal anti-reflection and anti-reflection effect. The nano-level inorganic film has a good anti-reflection and anti-reflection effect, and the transmittance can reach 99.5%.

[0028] (2) Compared with thermal evaporation and magnetron sputtering technology, ALD technology can provide better substrate adhesion. The present invention combines ALD technology by optimizing the pretreatment process of the glass substrate surface, that is, further promoting the uniform deposition of ALD film on the glass substrate surface through plasma activation, thereby increasing the substrate adhesion, which is crucial to improving the durability and stability of the film.

[0029] (3) By optimizing the ALD coating process, the present invention makes the TiO2 film have high oxygen sensitivity and exhibits a high response to O2, indicating that the ALD technology can be used to prepare high-quality TiO2 / SiO2 laminated films, making the coating deposition more uniform and dense, further improving the anti-reflection and anti-transmittance effect.

[0030] (4) The present invention effectively avoids the defects caused by excessive film deposition thickness, and changing the thickness of the laminated film will change its optical constants, which will directly affect the reflection, transmission and absorption characteristics of the film. According to the film microstructure and surface morphology, the reflectivity can reach the maximum or minimum value when specific interference conditions are met. When the total thickness of the film is 274nm, the reflectivity is below 0.5%, reaching the minimum value.

[0031] (5) The TiO2 / SiO2 film prepared by the ALD technology in the present invention has good environmental stability, which is crucial for outdoor applications and long-term stability.

[0032] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 It is a flow chart of Example 1 of a method for preparing an anti-reflection and anti-reflection film on the surface of photovoltaic encapsulation glass according to the present invention;

[0034] Figure 2 It is a structural schematic diagram of a second embodiment of an anti-reflection and anti-reflection film on the surface of photovoltaic encapsulation glass according to the present invention;

[0035] Figure 3 This is a graph showing the relationship between reflectivity and wavelength of a second embodiment of an anti-reflection and anti-reflection film on the surface of photovoltaic encapsulation glass according to the present invention;

[0036] Figure 4 The diagram is a simulated variation diagram of the relationship between reflectivity and wavelength of an embodiment of an anti-reflection and anti-reflection film on the surface of a photovoltaic encapsulation glass of the present invention, wherein (a) is embodiment 2, (b) is embodiment 3, (c) is embodiment 4, (d) is comparative example 1, and (e) is comparative example 2. DETAILED DESCRIPTION

[0037] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0038] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0039] Embodiment 1

[0040] like Figure 1 As shown, a method for preparing an anti-reflection and anti-reflection film on the surface of photovoltaic encapsulation glass comprises the following steps:

[0041] S1. Pre-cleaning of the surface of the glass substrate: Use deionized water to clean the surface of the glass substrate to remove impurities, then use an organic solvent to soak and clean the glass substrate, the organic solvent is ethanol or acetone, and dry after cleaning to remove surface chemical pollutants.

[0042] S2. Use a plasma generator to purge the surface of the glass substrate: Put the cleaned and dried glass substrate into the ALD chamber, and use the inductively coupled (ICP) plasma generator inside the ALD chamber to further remove impurities from the surface. Set the plasma power of the ICP plasma generator to 600W, and use oxygen / argon mixed plasma to purge the surface of the glass substrate. The plasma action time is 10min~20min. After the plasma treatment, the surface contamination particles of the glass substrate are further removed, and the adhesion of the film is further improved.

[0043] S3. Deposit an ALD-TiO2 seed layer on the surface of a glass substrate using atomic layer deposition technology: the temperature setting range of the ALD chamber is 90°C~120°C, and the optimal setting is 100°C; evacuate to 0Pa~20Pa. Use argon as a carrier gas to alternately introduce a titanium precursor and an oxidant, and cycle 216 cycles to deposit an ALD-TiO2 seed layer with a thickness of 16nm. In this embodiment, the titanium precursor is titanium tetrachloride (TiCl4) and the oxidant is water (H2O).

[0044] S4. According to a certain thickness ratio, an ALD-TiO2 / SiO2 composite layer with a thickness of 258 nm is deposited on the upper surface of the ALD-TiO2 seed layer to obtain an anti-reflection and anti-reflection film with a thickness of 274 nm. The details are as follows:

[0045] The temperature setting range of the ALD chamber is 90℃~120℃, and the optimal setting is 100℃; the chamber is vacuumed to 0Pa~20Pa.

[0046] Argon gas was used as a carrier, and a silicon precursor was introduced in the presence of plasma oxygen, and an ALD-SiO2 layer with a thickness of 40 nm was deposited after 276 cycles. In this embodiment, the silicon precursor was bis(diethylamino)silane (BDEAS), and the oxidant was plasma-enhanced oxygen.

[0047] The titanium precursor and the oxidant were introduced alternately in sequence using argon as a carrier gas, and an ALD-TiO2 layer with a thickness of 54 nm was deposited by 730 cycles.

[0048] Using argon as a carrier, silicon precursor was introduced in the presence of plasma oxygen, and an ALD-SiO2 layer with a thickness of 17 nm was obtained by deposition for 117 cycles.

[0049] The titanium precursor and the oxidant were introduced alternately in sequence using argon as a carrier gas, and an ALD-TiO2 layer with a thickness of 44 nm was deposited by 595 cycles.

[0050] Using argon as a carrier, silicon precursor was introduced in the presence of plasma oxygen, and an ALD-SiO2 layer with a thickness of 103 nm was deposited after 710 cycles.

[0051] Embodiment 2

[0052] like Figure 2 As shown, an anti-reflection and anti-reflection film with a total thickness of 274 nm prepared by the method of Example 1 includes a glass substrate, an ALD-TiO2 seed layer with a thickness of 16 nm, and an ALD-TiO2 / SiO2 composite layer with a thickness of 258 nm. Specifically, the thicknesses of the ALD-SiO2 layer are 40 nm, 54 nm, 17 nm, 44 nm, and 103 nm, respectively.

[0053] Embodiment 3

[0054] The difference from Example 2 is that the anti-reflection and anti-reflection film with a total thickness of 225 nm includes a glass substrate and an ALD-TiO2 seed layer with a thickness of 5 nm (68 cycles), a 30 nm ALD-SiO2 layer (207 cycles), a 45 nm ALD-TiO2 layer (608 cycles), a 15 nm ALD-SiO2 layer (103 cycles), a 35 nm ALD-TiO2 layer (473 cycles), and a 95 nm ALD-SiO2 layer (655 cycles).

[0055] Embodiment 4

[0056] The difference from Example 2 is that the anti-reflection and anti-reflection film with a total thickness of 250 nm includes a glass substrate and an ALD-TiO2 seed layer with a thickness of 10 nm (135 cycles), a 35 nm ALD-SiO2 layer (241 cycles), a 50 nm ALD-TiO2 layer (676 cycles), a 15 nm ALD-SiO2 layer (103 cycles), a 40 nm ALD-TiO2 layer (541 cycles), and a 100 nm ALD-SiO2 layer (690 cycles).

[0057] Comparative Example 1

[0058] The difference from Example 2 is that the anti-reflection and anti-reflection film with a total thickness of 300 nm includes a glass substrate and an ALD-TiO2 seed layer with a thickness of 20 nm (270 cycles), a 45 nm ALD-SiO2 layer (310 cycles), a 60 nm ALD-TiO2 layer (811 cycles), a 20 nm ALD-SiO2 layer (138 cycles), a 50 nm ALD-TiO2 layer (676 cycles), and a 105 nm ALD-SiO2 layer (724 cycles).

[0059] Comparative Example 2

[0060] The difference from Example 2 is that the anti-reflection and anti-reflection film with a total thickness of 325 nm includes a glass substrate and an ALD-TiO2 seed layer with a thickness of 25 nm (338 cycles), a 50 nm ALD-SiO2 layer (345 cycles), a 60 nm ALD-TiO2 layer (811 cycles), a 25 nm ALD-SiO2 layer (172 cycles), a 55 nm ALD-TiO2 layer (743 cycles), and a 110 nm ALD-SiO2 layer (759 cycles).

[0061] Experimental Testing

[0062] The glass substrate sample covered with the anti-reflection and anti-reflection film obtained in Example 2 was placed in a micro-spectrophotometer for reflectivity testing. During the test, three points (Point 1, Point 2 and Point 3) were selected for measurement. The test results are shown in FIG. Figure 3 shown.

[0063] Through analysis, we know that within the wavelength range of 450~700nm, the reflectivity of the glass substrate covered with ALD-TiO2 / SiO2 stack is below 0.5%, that is, when the glass substrate is coated on one side, the transmittance can reach 99.5% after deducting the slight absorption and scattering effects, which shows that the prepared film has a very high anti-reflection and anti-transmission effect. In addition, the curves fitted by the three points Point1, Point2 and Point3 on the surface of the glass substrate are close, indicating that the ALD-TiO2 / SiO2 stack grows uniformly on the glass substrate.

[0064] The formulations in Example 2, Example 3, Example 4, Comparative Example 1 and Comparative Example 2 were used to perform reflectivity simulation tests using optical film design software. The simulation results are as follows: Figure 4 shown.

[0065] Through analysis, it can be known that: within the wavelength range of 450~700nm, the reflectivity of Example 2 is still below 0.5%, which is basically consistent with the reflectivity test results of the microspectrophotometer, so the authenticity of the reflectivity simulation test of the optical film design software is proved. The reflectivity of Example 3 is below 2.6%, the reflectivity of Example 4 is below 1%, the reflectivity of Comparative Example 1 is below 15%, and the reflectivity of Comparative Example 2 is below 45%. This is because the refractive index of TiO2 and SiO2 is different. Changing the thickness of the laminated film will change the optical constants (refractive index and extinction coefficient) of the entire film. The change of the optical constants will directly affect the reflection, transmission and absorption characteristics of the film. In addition, the reflectivity of the film is related to the interference effect of the light wave inside the film. When the light wave is reflected between different medium interfaces, the thickness of the film determines the path length of the light wave propagating inside the film, thereby affecting the interference conditions and then affecting the reflectivity. The relationship between the reflectivity of a film and the wavelength of incident light shows that, under the condition of a certain film thickness, the reflectivity varies with the wavelength according to the microstructure and surface morphology of the film (for example, when the SiO2 content increases, the surface roughness of the film increases). Only when specific interference conditions are met can the reflectivity reach the maximum or minimum value.

[0066] Therefore, the present invention adopts the above-mentioned anti-reflection and anti-reflection film on the surface of photovoltaic encapsulation glass and the preparation method. The film has excellent anti-reflection and anti-reflection effects, and the film has high stability, uniformity and durability, effectively reducing light loss and thereby improving photoelectric conversion efficiency.

[0067] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing an anti-reflection and anti-reflection film on the surface of photovoltaic encapsulation glass, characterized in that: The following steps are involved: S1. Pre-cleaning of the glass substrate surface; S2, using a plasma generating device to purge the surface of the glass substrate; S3, depositing an ALD-TiO2 seed layer on the surface of the glass substrate using atomic layer deposition technology; S4, depositing an ALD-TiO2 / SiO2 composite layer on the upper surface of the ALD-TiO2 seed layer at a certain thickness ratio to obtain an anti-reflection and anti-reflection film; The anti-reflection and anti-reflection film comprises a glass substrate and an ALD-TiO2 seed layer and an ALD-TiO2 / SiO2 composite layer sequentially arranged on the surface of the glass substrate, wherein the ALD-TiO2 / SiO2 composite layer comprises a plurality of ALD-SiO2 layers, and an ALD-TiO2 layer is arranged between the ALD-SiO2 layers; The number of the ALD-SiO2 layers is three, and the thickness ratio of the ALD-TiO2 seed layer, ALD-SiO2 layer, ALD-TiO2 layer, ALD-SiO2 layer, ALD-TiO2 layer, and ALD-SiO2 layer is 5~16:30~40:45~54:15~17:35~44:95~103.

2. The method for preparing an anti-reflection and anti-reflection film on the surface of photovoltaic encapsulation glass according to claim 1, characterized in that: S1 is specifically: Deionized water is used to clean the surface of the glass substrate to remove impurities, and then the glass substrate is soaked and cleaned with an organic solvent, and then dried after cleaning.

3. The method for preparing an anti-reflection and anti-reflection film on the surface of photovoltaic encapsulation glass according to claim 1, characterized in that: S2 is specifically: The glass substrate was placed in the ALD chamber, and the plasma power of the plasma generator was set to 600 W. The surface of the glass substrate was purged with oxygen-argon mixed plasma for 10 min to 20 min.

4. The method for preparing an anti-reflection and anti-reflection film on the surface of photovoltaic encapsulation glass according to claim 1, characterized in that: S3 is specifically: In the ALD chamber, the temperature range is set to 90℃~120℃, the vacuum is 0Pa~20Pa, and argon is used as a carrier gas to alternately introduce a titanium precursor and an oxidant, and the ALD-TiO2 seed layer is obtained by multiple cycles of deposition.

5. The method for preparing an anti-reflection and anti-reflection film on the surface of photovoltaic encapsulation glass according to claim 4, characterized in that: In S3, the set temperature is 100°C.

6. The method for preparing an anti-reflection and anti-reflection film on the surface of photovoltaic encapsulation glass according to claim 4, characterized in that: In S3, the range of the multiple deposition cycles is 100-1000 cycles.

7. The method for preparing an anti-reflection and anti-reflection film on the surface of photovoltaic encapsulation glass according to claim 1, characterized in that: S4 is specifically: S41, in the ALD chamber, using argon as a carrier, introducing a silicon precursor in the presence of plasma oxygen, and performing multiple cycles of deposition to obtain an ALD-SiO2 layer; S42, using argon as a carrier gas, alternately introducing a titanium precursor and an oxidant, and performing multiple cycles of deposition to obtain an ALD-TiO2 layer; S43, taking a layer of ALD-TiO2 deposited by multiple cycles and a layer of ALD-SiO2 deposited by multiple cycles as a whole, repeating several layers to obtain an ALD-TiO2 / SiO2 composite layer.

8. An anti-reflection and anti-reflection film prepared by the method for preparing an anti-reflection and anti-reflection film on the surface of photovoltaic encapsulation glass according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Method for forming durable dual-layer antireflection film on surface of soda-lime glass

    CN102910835A

  • Photovoltaic glass antireflection film

    CN108424007A

Cited By

  • Anti-reflection film on surface of optical instrument and preparation method of anti-reflection film

    CN121634356A